2012
DOI: 10.2174/138920012798918471
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein Plasticity in Computational Rationalization Studies on Regioselectivity in Testosterone Hydroxylation by Cytochrome P450 BM3 Mutants

Abstract: Recently, it was found that mutations in the binding cavity of drug-metabolizing Cytochrome P450 BM3 mutants can result in major changes in regioselectivity in testosterone (TES) hydroxylation. In the current work, we report the intrinsic reactivity of TES' C-H bonds and our attempts to rationalize experimentally observed changes in TES hydroxylation using a protein structure-based in silico approach, by setting up and employing a combined Molecular Dynamics (MD) and ligand docking approach to account for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The application of the high-scoring poses has proved to be effective in the SOM prediction of specific CYPs substrates, such as the metabolism of tramadol in CYP2D6 and the metabolism of testosterone in P450 BM3. 57,58 However, our results revealed that their positive results were in some special cases. There were only ∼30% of tested CYP3A4 substrates that could position the SOM at the closest place to Fe within the top three poses (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the high-scoring poses has proved to be effective in the SOM prediction of specific CYPs substrates, such as the metabolism of tramadol in CYP2D6 and the metabolism of testosterone in P450 BM3. 57,58 However, our results revealed that their positive results were in some special cases. There were only ∼30% of tested CYP3A4 substrates that could position the SOM at the closest place to Fe within the top three poses (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of ensemble docking has since then been applied more often to CYP enzymes, in particular for the bacterial CYP102A1 (CYP BM3) [49] and for the human isoforms 2D6 [50] and 3A4 [51]. In the latter study, 16 substrates were docked into 125 protein structures as obtained from MD simulations.…”
Section: Protein Flexibilitymentioning
confidence: 99%
“…The advantage of bacterial CYPs could be the ease of expression and the higher catalytic efficiency, although the wild-type substrate specificity may be unfavorable for the majority of applications. Various drug metabolizing mutants of cytochrome CYP102A1 from Bacillus megaterium (CYP BM3) have been described, and from the onset, computational tools were integrated in the rationalization and design of novel mutants [49,71,72]. Two mutants of CYPBM3 were experimentally shown to catalyze the stereospecific hydroxylation of α-ionones [73].…”
Section: Effect Of Mutationsmentioning
confidence: 99%
“…Whereas wild-type (WT) BM3 only accepts long fatty acids as substrates, many successful protein engineering studies have been reported over the last years that report mutants of BM3 able to hydroxylate drugs and drug-like compounds with high activity and with regio-and/or stereo-selectivity [11][12][13][14][15][16][17][18][19][20][21]. However, rationally predicting novel mutants with enhanced selectivity and/or activity is still difficult especially when considering the flexibility of their active site and because they can typically bind a variety of substrates in multiple binding poses [18,[22][23][24][25][26]. In the present combined experimental and computational study we report and study the biocatalytic activity for (regioselective) 5′ methyl-hydroxylation of FLX by CYP BM3 mutants M11, M11 L437E and M11 L437A.…”
Section: Introductionmentioning
confidence: 99%